Gait analysis using digital biomarkers including smart shoes in lumbar spinal canal stenosis: a scoping review - Morimoto, Tadatsugu; Hirata, Hirohito; Kobayashi, Takaomi; Tsukamoto, Masatsugu; Yoshihara, Tomohito; Toda, Yu; Mawatari, Masaaki (Frontiers in Medicine, 2023)
Lumbar spinal canal stenosis (LSS) is characterized by gait disturbance, and objective quantitative gait analysis is useful for diagnosis and treatment. This study aimed to provide a review of objective quantitative gait analysis in LSS and note the current status and potential of smart shoes in diagnosing and treating LSS. The characteristics of gait deterioration in LSS include decreased gait velocity and asymmetry due to neuropathy (muscle weakness and pain) in the lower extremities. Previous laboratory objective and quantitative gait analyses mainly comprised marker-based three-dimensional motion analysis and ground reaction force. However, workforce, time, and costs pose some challenges. Recent developments in wearable sensor technology and markerless motion analysis systems have made gait analysis faster, easier, and less expensive outside the laboratory. Smart shoes can provide more accurate gait information than other wearable sensors. As only a few reports exist on gait disorders in patients with LSS, future studies should focus on the accuracy and cost-effectiveness of gait analysis using smart shoes.